Neuroprotection of Adult Human Neurons Against Ischemia by Hypothermia and Alkalinization - Reyes, Onix; Sosa, Ivan; Kuffler, Damien P. (Puerto Rico Health Sciences Journal, 2006)
Ischemia of intact dorsal root ganglia (DRG) in situ leads to massive neuron death due to ischemiatriggered secondary events, such as massive release of excitatory amino acids from the neurons, their excessive accumulation and activation of neuron NMDA and other receptors, acidification, and loss of calcium homeostasis. The present experiments tested whether hypothermia and alkalinization, separately or combined, provide neuroprotection against 1-4 hours of ischemia to the neurons within intact DRG acutely removed from organ donors. DRG under hypothermic (20-15oC) or alkaline (pH 8.0 - 9.3) conditions yielded more viable neurons than DRG maintained under physiological conditions (37oC/pH 7.4), 4.1-fold vs. 7.8-fold respectively, but, hypothermia and alkalinization combined (20oC/pH 9.3) increased the yield of viable neurons 26-fold compared to DRG maintained under physiological conditions. These results show that combined hypothermia and alkalinization provide adult human DRG neurons significant neuroprotection against ischemia, and ischemia-induced causes of neuron death.